The Julanda of Oman - Wilkinson, J. C. (The Journal of Oman Studies, 1975)
Two families of south-east Arabia came to bear the title Julandā (var. Julundā), the Julandā b. Karkar who feature in the history of the Gulf from pre-Islamic until Būyid times, and the Ma’wali Julandā who more or less controlled the Oman (correctly ’Umān) region until the full establishment of the Ibāḍi Imamate at the end of the eighth century. It is with the latter that this study is concerned.